Comparing complex perspectives on obesity drivers: action‐driven communities and evidence‐oriented experts. (22nd November 2018) - McGlashan, J.; Hayward, J.; Brown, A.; Owen, B.; Millar, L.; Johnstone, M.; Creighton, D.; Allender, S.
Summary: Introduction: The Foresight obesity map represents an expert‐developed systems map describing the complex drivers of obesity. Recently, community‐led causal loop diagrams have been developed to support community‐based obesity prevention interventions. This paper presents a quantitative comparison between the Foresight obesity systems map and a community‐developed map of the drivers of obesity. Methods: Variables from a community‐developed map were coded against the thematic clusters defined in the Foresight map to allow comparison of their sizes and strength of adjoining causal relationships. Central variables were identified using techniques from network analysis. These properties were compared to understand the similarities and differences between the systems as defined by the two groups. Results: The community map focused on environmental influences, such as built physical activity environment (18% of variables) and social psychology (38%). The Foresight map's largest cluster was physiology (23%), a minimal focus in the community map (2%). Network analysis highlighted media and available time within both maps, but variables related to school and sporting club environments were unique to the community map. Conclusion: Community stakeholders focus on modifiable social and environmental drivers of obesity. Capturing local perspectives is critical when using systems maps to guide community‐based obesity prevention.